HISTORY, OVERVIEW AND THE USE OF THE GRAMMAR TRANSLATION METHOD - Abrueva, Malika Zafarovna (Educational Research in Universal Sciences, 2023)
The Grammar Translation Method (GTM) has a long history, but has recently fallen out of favour as an effective method of second language acquisition. This article examines the origins and history of the GTM, its main features and contemporary criticism of the method. Particular attention is paid to the history and application of the grammatical translation method, as well as how it sometimes affects pedagogy.